Marketing Strategy for Abon Oncom Products Pasireungit Ki Haji as a Typical Food in the City of Sumedang - Ginanjar, Yayat; Kusumawardani, Rani; Sari, Melita Dewita; Sihombing, Lusiana; Fitriani, Fitriani (Journal of Bussines Management Basic, 2025)
This research aims to analyze the marketing strategy for the product Pasireungit Kihaji abon oncom as a typical food in the city of Sumedang before and after the Covid-19 pandemic. Using a qualitative approach, this research explores changes in marketing strategies implemented bymanufacturers in facing the challenges posed by the pandemic. Research data was collected through interviews with business owners. The results of the research show that before the pandemic, the marketing strategy for Pasireungit Kihaji abon oncom products focused more on direct sales and participating in exhibition events. However, after the pandemic, there has been a significant shift towards digital marketing, including social media users and marketplace platforms to reach a wider range of consumers. Apart from that, product and package wider range of consumers. Apart from that, product and packag innovation is also the main focus to attract consumer attention during the period of adapting to new habits. This research concludes that quick and effective adaptation of marketing strategies is very important for the sustainability of the Abon Oncom Pasireungit KiHaji business amidst changes in consumer behavior due to the Covid -19 pandemic. It is hoped that these findings can become a reference for other culinary business actors in facing similar situations in the future